Attribution of reasons for religious beliefs in four ethnic groups - Keats, D.M.; Keats , J.A.; Mohammad Hj. Yusuf, (Universiti Kebangsaan Malaysia, 1976)
Approximately 120 adolescents from each of four ethnic groups - Malay, Chinese, Indian and Australian - stratified by age and sex, were individually asked to rank six postulated reasons why people are religious. In brief, the alternatives related to God's will, family, own effort, natural gift, own choice and luck. The alternative 'luck' was rejected by all subject in all groups. The results seemed to be consistent with the likely religious influences in the ethnic groups. The most significant finding was that age and sex as individual differences variables correlated with attribution in different ways and to different extents in the four groups. The result were related to Weiner's attribution theory and to Herbst's findings on relationships between variables for particular individuals.